Identifying the Psychological Dimensions of Academic Resilience through Principal Component Analysis - Dedy Surya; Muhammad Athaya Rizqilla; Fahru Azra’i Ansor; Tio Setiawan (Program Studi Psikologi Fakultas Kedokteran Universitas Malikussaleh, 2025)
This study aims to identify the core dimensions underlying academic resilience through exploratory confirmatory factor analysis. A total of 27 items representing psychological aspects such as perseverance, self-regulation, self-efficacy, and social support were analyzed using Principal Component Analysis (PCA) with Varimax rotation and Kaiser normalization. The results revealed ten principal components with significant factor loadings on several items, with rotation converging in 21 iterations. These components represent essential aspects of academic resilience, including adaptability, emotional control, achievement motivation, and social support. The findings provide empirical evidence for developing a valid and reliable instrument for measuring academic resilience within the context of higher education in Indonesia.